2021
DOI: 10.1038/s41598-021-82590-w
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-induced negative magnetic susceptibility in epoxy/magnetite nanocomposites

Abstract: The epoxy/magnetite nanocomposites express superparamagnetism under a static or low-frequency electromagnetic field. At the microwave frequency, said the X-band, the nanocomposites reveal an unexpected diamagnetism. To explain the intriguing phenomenon, we revisit the Debye relaxation law with the memory effect. The magnetization vector of the magnetite is unable to synchronize with the rapidly changing magnetic field, and it contributes to diamagnetism, a negative magnetic susceptibility for nanoparticles. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The pattern of susceptibility-frequency change in the Ni and Fe sample is consistent with the of results of R.F. Jardim et al [20] and Ching-Ray Chang et al [21] observed on Ni and nano magnetite powder sample.…”
Section: Calibration Of the Ac Susceptometer And Measurement Of Stand...supporting
confidence: 90%
“…The pattern of susceptibility-frequency change in the Ni and Fe sample is consistent with the of results of R.F. Jardim et al [20] and Ching-Ray Chang et al [21] observed on Ni and nano magnetite powder sample.…”
Section: Calibration Of the Ac Susceptometer And Measurement Of Stand...supporting
confidence: 90%
“…In this case, it is not clear whether the magnetic particles move themselves or move by the shape change of the magnetic elastomer. The relative magnetic susceptibility of carbonyl iron is 600-fold higher than that of epoxy resin . It can be considered that the magnetic effect of resin can be neglected in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The relative magnetic susceptibility of carbonyl iron is 600-fold higher than that of epoxy resin. 33 It can be considered that the magnetic effect of resin can be neglected in this experiment. An electromagnet (5201 horizontal projected field, GMW) was used to generate magnetic fields using a bipolar power supply (BOP20-20DL, KEPCO) while monitoring the output current with a digital multimeter (Keithley 2100).…”
Section: Methodsmentioning
confidence: 99%